A Case Report of Avian Polyomavirus Infection in a Blue Fronted Parrot (Amazona aestiva) Associated with Anemia - Natalia Azevedo Philadelpho; Marta B. Guimarães; Antonio J. Piantino Ferreira (Case Reports in Veterinary Medicine)
An adult Blue Fronted Amazon parrot (A. aestiva) presenting with emesis, apathy, undigested seed in feces, and severe anemia was treated for approximately 2 months. Upon radiographic examination, an enlarged kidney was the only alteration. PCR for avian Bornavirus, Circovirus, and Polyomavirus was performed for the feces and blood. The results were positive for APV in both samples and negative for the other viruses. After 6 months, the feces from the same animal were negative for APV. Because the animal was positive for APV in both the feces and the blood, it is likely that these clinical symptoms were due to Polyomavirus infection. Severe anemia is an unusual clinical sign of Polyomavirus, and this study aims to identify novel differential diagnostic criteria for the disease.